Glass-ceramics and glass-ceramic articles

CN122977705APending Publication Date: 2026-10-27CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510529470.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

虽然玻璃陶瓷越来越抗摔,但相比于高铝玻璃,现有技术中的玻璃陶瓷抗划性能较差,光透过率等难以达到应用于盖板材料的要求

Benefits of technology

[0054]本发明的有益效果是:通过合理的组分设计,本发明获得的玻璃陶瓷和玻璃陶瓷制品具有优异的抗划性能和光透过率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977705A_ABST
    Figure CN122977705A_ABST
Patent Text Reader

Abstract

The present application provides a glass ceramic and a glass ceramic product with excellent light transmittance and scratch resistance. The glass ceramic product contains, in terms of percentage by weight, SiO2: 43-50%; Al2O3: 27.5-35%; ZnO: 8.5-12%; Li2O: 0.1-5%; and TiO2: 2-6%. Through reasonable component design, the glass ceramic and the glass ceramic product obtained by the present application have excellent scratch resistance and light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a glass ceramic, and more particularly to a glass ceramic and glass ceramic articles with excellent light transmittance and scratch resistance. Background Technology

[0002] Glass-ceramics are materials that crystallize within glass through heat treatment, resulting in superior mechanical properties compared to conventional glass. Their bending resistance, abrasion resistance, and impact resistance are significantly better than those of conventional glass. With the rise and development of consumer electronics, the application of glass-ceramics is expanding, including devices such as LED and LCD displays, computer monitors, and portable electronic products (such as mobile phones, tablets, and personal media terminals). While glass-ceramics are becoming increasingly impact-resistant, their scratch resistance is still relatively poor compared to high-alumina glass, and their light transmittance is insufficient for use as cover materials. Therefore, developing a glass-ceramic with excellent scratch resistance and light transmittance has become a goal pursued by researchers. Summary of the Invention

[0003] The technical problem to be solved by the present invention is to provide a glass ceramic and glass ceramic products with excellent light transmittance and scratch resistance.

[0004] The technical solution adopted by this invention to solve the technical problem is:

[0005] (1) Glass ceramic products, whose components are expressed as weight percentages, contain: SiO2: 43-50%; Al2O3: 27.5-35%; ZnO: 8.5-12%; Li2O: 0.1-5%; TiO2: 2-6%.

[0006] (2) The glass-ceramic product according to (1) further comprises, by weight percentage: MgO: 0-5%; and / or Na2O: 0-7%; and / or ZrO2: 0-5%; and / or K2O: 0-3%; and / or B2O3: 0-4%; and / or CaO+BaO+SrO: 0-5%; and / or Ln2O3: 0-8%; and / or clarifying agent: 0-2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0007] (3) Glass ceramic products, the components of which are expressed by weight percentage as follows: SiO2: 43-50%; Al2O3: 27.5-35%; ZnO: 8.5-12%; Li2O: 0.1-5%; TiO2: 2-6%; MgO: 0-5%; Na2O: 0-7%; ZrO2: 0-5%; K2O: 0-3%; B2O3: 0-4%; CaO+BaO+SrO: 0-5%; Ln2O3: 0-8%; clarifying agent: 0-2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0008] (4) A glass-ceramic product containing SiO2, Al2O3, ZnO, Li2O and TiO2, wherein the glass-ceramic product contains a spinel crystal phase.

[0009] (5) A glass-ceramic product containing a spinel crystal phase, wherein the grain size of the glass-ceramic product is less than 70 nm.

[0010] (6) A glass-ceramic product containing a spinel crystal phase, wherein the Young's modulus of the glass-ceramic product is 80 to 105 GPa.

[0011] (7) Glass ceramic products containing spinel crystal phase, glass ceramic products with a thickness of less than 2.0 mm, and an average light transmittance of more than 85% at wavelengths of 400 to 800 nm.

[0012] (8) A glass-ceramic product containing SiO2, Al2O3 and ZnO, wherein the surface stress of the glass-ceramic product is above 40 MPa.

[0013] (9) The glass-ceramic product according to any one of (4) to (8) contains, by weight percentage: SiO2: 43-50%; Al2O3: 27.5-35%; ZnO: 8.5-12%; Li2O: 0.1-5%; TiO2: 2-6%.

[0014] (10) The glass-ceramic article according to any one of (4) to (9) further comprises, by weight percentage: MgO: 0-5%; and / or Na2O: 0-7%; and / or ZrO2: 0-5%; and / or K2O: 0-3%; and / or B2O3: 0-4%; and / or CaO+BaO+SrO: 0-5%; and / or Ln2O3: 0-8%; and / or clarifying agent: 0-2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0015] (11) The glass-ceramic product according to any one of (1) to (10) has components expressed as a weight percentage, wherein: (ZnO+MgO+SiO2) / Al2O3 is 1.5 to 2.15, preferably (ZnO+MgO+SiO2) / Al2O3 is 1.6 to 2.15, and more preferably (ZnO+MgO+SiO2) / Al2O3 is 1.8 to 2.1.

[0016] (12) The glass-ceramic article according to any one of (1) to (10) has components expressed as a weight percentage, wherein: Al2O3 / Li2O is 11.0 to 60.0, preferably Al2O3 / Li2O is 12.0 to 40.0, and more preferably Al2O3 / Li2O is 13.0 to 20.0.

[0017] (13) The glass-ceramic article according to any one of (1) to (10) has components expressed as weight percentages, wherein: (ZnO+MgO) / (Li2O+Na2O) is 1.5 to 5.0, preferably (ZnO+MgO) / (Li2O+Na2O) is 1.7 to 4.5, and more preferably (ZnO+MgO) / (Li2O+Na2O) is 1.8 to 4.0.

[0018] (14) The glass-ceramic article according to any one of (1) to (10) has its components expressed as a weight percentage, wherein: (TiO2+ZrO2) / (Li2O+Na2O) is 0.5 to 5.0, preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 3.0, and more preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 1.5.

[0019] (15) The glass-ceramic article according to any one of (1) to (10) has the following composition expressed as a weight percentage: SiO2 / Al2O3 is 1.3 to 1.8, preferably SiO2 / Al2O3 is 1.4 to 1.7, and more preferably SiO2 / Al2O3 is 1.45 to 1.67.

[0020] (16) The glass-ceramic article according to any one of (1) to (10) has its components expressed as a weight percentage, wherein: (Al2O3+Ln2O3) / Li2O is 14.5 to 100.0, preferably (Al2O3+Ln2O3) / Li2O is 15.0 to 60.0, more preferably (Al2O3+Ln2O3) / Li2O is 16.0 to 40.0, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0021] (17) The glass-ceramic article according to any one of (1) to (10), wherein the components are expressed as weight percentages, wherein: SiO2: 44-49%, preferably SiO2: 44-48%; and / or Al2O3: 28-34%, preferably Al2O3: 28-33%; and / or Li2O: 1-5%, preferably Li2O: 1-4%; and / or ZnO: 9-12%, preferably ZnO: 9-11%; and / or TiO2: 2-5%, preferably TiO2: 2-4%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or Ln2O3: 0.1-6%, preferably... Ln2O3: 0.1-3%; and / or ZrO2: 0.5-4%, preferably ZrO2: 1-3%; and / or Na2O: 1-6%, preferably Na2O: 2-5%; and / or MgO: 1-4%, preferably MgO: 1-3%; and / or B2O3: 0-2%, preferably B2O3: 0-1%; and / or CaO+BaO+SrO: 0-4%, preferably CaO+BaO+SrO: 0-2%; and / or clarifying agent: 0-1%, preferably clarifying agent: 0-0.5%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0022] (18) The glass-ceramic article according to any one of (1), (2), (4) to (10) contains, by weight percentage: Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%, more preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%, and even more preferably does not contain Nb2O5, and / or does not contain WO3, and / or does not contain Bi2O3, and / or does not contain Ta2O5, and / or does not contain TeO2.

[0023] (19) The glass-ceramic article according to any one of (1) to (10) is free from P2O5 and / or free from B2O3 and / or free from SnO2 and / or free from SnO.

[0024] (20) The glass-ceramic article according to any one of (1) to (10), wherein the glass-ceramic article contains a spinel crystal phase, preferably having a higher weight percentage of the spinel crystal phase than other crystal phases, more preferably having a spinel crystal phase accounting for 20 to 50% of the weight percentage of the glass-ceramic article, even more preferably having a spinel crystal phase accounting for 30 to 50% of the weight percentage of the glass-ceramic article, and even more preferably having a spinel crystal phase accounting for 30 to 45% of the weight percentage of the glass-ceramic article.

[0025] (21) The glass-ceramic product according to (20) wherein the spinel crystal phase is ZnAl2O4.

[0026] (22) The glass-ceramic article according to any one of (1) to (10) is free from spodumene crystal phase and / or free from zirconium oxide crystal phase and / or free from quartz crystal phase and / or free from quartz solid solution crystal phase and / or free from Zn2SiO4 crystal phase.

[0027] (23) The glass-ceramic article according to any one of (1) to (10), wherein the grain size of the glass-ceramic article is 70 nm or less, preferably 60 nm or less, more preferably less than 50 nm, and even more preferably 48 nm or less; and / or the surface stress is 40 MPa or more, preferably 80 to 200 MPa, more preferably 100 to 200 MPa; and / or the drop ball test height is 800 mm or more, preferably 1000 mm or more, more preferably 1200 mm or more; and / or The impact resistance is 800 mm or more, preferably 1000 mm or more, more preferably 1200 mm or more; and / or the compressive strength is 200 N or more, preferably 250 N or more, more preferably 300 N or more; and / or the Young's modulus E is 80–105 GPa, preferably 85–105 GPa, more preferably 90–105 GPa; and / or the scratch width is less than 30 μm, preferably less than 25 μm, more preferably less than 20 μm; and / or the Vickers hardness is 600 kgf / mm². 2 The above values ​​are preferably 650–800 kgf / mm². 2 More preferably, it is 680–800 kgf / mm 2 ; and / or glass-ceramic products with a thickness of less than 2.0 mm, having an average light transmittance of 85% or more at a wavelength of 400 to 800 nm, preferably 87% or more, and more preferably 88% or more.

[0028] (24) Glass ceramics, whose components are expressed as weight percentages, contain: SiO2: 43-50%; Al2O3: 27.5-35%; ZnO: 8.5-12%; Li2O: 0.1-5%; TiO2: 2-6%.

[0029] (25) The glass ceramic according to (24) further comprises, by weight percentage: MgO: 0-5%; and / or Na2O: 0-7%; and / or ZrO2: 0-5%; and / or K2O: 0-3%; and / or B2O3: 0-4%; and / or CaO+BaO+SrO: 0-5%; and / or Ln2O3: 0-8%; and / or clarifying agent: 0-2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0030] (26) A glass ceramic, the composition of which, by weight percentage, is composed of SiO2: 43-50%; Al2O3: 27.5-35%; ZnO: 8.5-12%; Li2O: 0.1-5%; TiO2: 2-6%; MgO: 0-5%; Na2O: 0-7%; ZrO2: 0-5%; K2O: 0-3%; B2O3: 0-4%; CaO+BaO+SrO: 0-5%; Ln2O3: 0-8%; and clarifying agent: 0-2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0031] (27) A glass ceramic containing SiO2, Al2O3, ZnO, Li2O and TiO2, wherein the glass ceramic contains a spinel crystal phase.

[0032] (28) A glass ceramic containing a spinel phase, wherein the grain size of the glass ceramic is less than 70 nm.

[0033] (29) A glass-ceramic containing a spinel phase, wherein the Young's modulus of the glass-ceramic is 80 to 105 GPa.

[0034] (30) Glass ceramics containing SiO2, Al2O3 and ZnO, with a thickness of less than 2.0 mm, and an average light transmittance of more than 85% at wavelengths of 400 to 800 nm.

[0035] (31) A glass-ceramic, comprising SiO2, Al2O3, and ZnO, wherein the Vickers hardness of the glass-ceramic is 500 kgf / mm. 2 above.

[0036] (32) The glass ceramic according to any one of (27) to (31) contains, by weight percentage: SiO2: 43 to 50%; Al2O3: 27.5 to 35%; ZnO: 8.5 to 12%; Li2O: 0.1 to 5%; TiO2: 2 to 6%.

[0037] (33) The glass ceramic according to any one of (27) to (32) further comprises, by weight percentage: MgO: 0-5%; and / or Na2O: 0-7%; and / or ZrO2: 0-5%; and / or K2O: 0-3%; and / or B2O3: 0-4%; and / or CaO+BaO+SrO: 0-5%; and / or Ln2O3: 0-8%; and / or clarifying agent: 0-2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0038] (34) The glass ceramic according to any one of (24) to (33) has the following composition expressed as a weight percentage: (ZnO+MgO+SiO2) / Al2O3 is 1.5 to 2.15, preferably (ZnO+MgO+SiO2) / Al2O3 is 1.6 to 2.15, and more preferably (ZnO+MgO+SiO2) / Al2O3 is 1.8 to 2.1.

[0039] (35) The glass ceramic according to any one of (24) to (33) has components expressed as weight percentages, wherein: Al2O3 / Li2O is 11.0 to 60.0, preferably Al2O3 / Li2O is 12.0 to 40.0, and more preferably Al2O3 / Li2O is 13.0 to 20.0.

[0040] (36) The glass ceramic according to any one of (24) to (33) has the following composition expressed as a weight percentage: (ZnO+MgO) / (Li2O+Na2O) is 1.5 to 5.0, preferably (ZnO+MgO) / (Li2O+Na2O) is 1.7 to 4.5, and more preferably (ZnO+MgO) / (Li2O+Na2O) is 1.8 to 4.0.

[0041] (37) The glass ceramic according to any one of (24) to (33) has its components expressed as weight percentages, wherein: (TiO2+ZrO2) / (Li2O+Na2O) is 0.5 to 5.0, preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 3.0, and more preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 1.5.

[0042] (38) The glass ceramic according to any one of (24) to (33) has the following composition expressed as a weight percentage: SiO2 / Al2O3 is 1.3 to 1.8, preferably SiO2 / Al2O3 is 1.4 to 1.7, and more preferably SiO2 / Al2O3 is 1.45 to 1.67.

[0043] (39) The glass ceramic according to any one of (24) to (33) has its components expressed as a weight percentage, wherein: (Al2O3+Ln2O3) / Li2O is 14.5 to 100.0, preferably (Al2O3+Ln2O3) / Li2O is 15.0 to 60.0, more preferably (Al2O3+Ln2O3) / Li2O is 16.0 to 40.0, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0044] (40) The glass-ceramic according to any one of (24) to (33), wherein the components are expressed in weight percentages, wherein: SiO2: 44-49%, preferably SiO2: 44-48%; and / or Al2O3: 28-34%, preferably Al2O3: 28-33%; and / or Li2O: 1-5%, preferably Li2O: 1-4%; and / or ZnO: 9-12%, preferably ZnO: 9-11%; and / or TiO2: 2-5%, preferably TiO2: 2-4%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or Ln2O3: 0.1-6%, preferably Ln2O3: 0.1-6%. Ln2O3: 0.1-3%; and / or ZrO2: 0.5-4%, preferably ZrO2: 1-3%; and / or Na2O: 1-6%, preferably Na2O: 2-5%; and / or MgO: 1-4%, preferably MgO: 1-3%; and / or B2O3: 0-2%, preferably B2O3: 0-1%; and / or CaO+BaO+SrO: 0-4%, preferably CaO+BaO+SrO: 0-2%; and / or clarifying agent: 0-1%, preferably clarifying agent: 0-0.5%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

[0045] (41) The glass ceramic according to any one of (24), (25), (27) to (33) contains, by weight percentage: Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%, more preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%, and even more preferably does not contain Nb2O5, and / or does not contain WO3, and / or does not contain Bi2O3, and / or does not contain Ta2O5, and / or does not contain TeO2.

[0046] (42) The glass ceramic according to any one of (24) to (33) wherein the glass ceramic does not contain P2O5, and / or does not contain B2O3, and / or does not contain SnO2, and / or does not contain SnO.

[0047] (43) The glass ceramic according to any one of (24) to (33), wherein the glass ceramic contains a spinel crystal phase, preferably having a higher weight percentage of the spinel crystal phase than other crystal phases, more preferably having a spinel crystal phase accounting for 20 to 50% of the weight percentage of the glass ceramic, even more preferably having a spinel crystal phase accounting for 30 to 50% of the weight percentage of the glass ceramic, and even more preferably having a spinel crystal phase accounting for 30 to 45% of the weight percentage of the glass ceramic.

[0048] (44) According to the glass ceramic of (43), the spinel crystal phase is ZnAl2O4.

[0049] (45) The glass ceramic according to any one of (24) to (33) is free from spodumene crystal phase and / or free from zirconium oxide crystal phase and / or free from quartz crystal phase and / or free from quartz solid solution crystal phase and / or free from Zn2SiO4 crystal phase.

[0050] (46) The glass-ceramic according to any one of (24) to (33), wherein the grain size of the glass-ceramic is 70 nm or less, preferably 60 nm or less, more preferably less than 50 nm, and even more preferably 48 nm or less; and / or the Vickers hardness is 500 kgf / mm. 2 The above values ​​are preferably 600–750 kgf / mm². 2 More preferably, it is 650–750 kgf / mm 2 ; and / or a Young's modulus of 80 to 105 GPa, preferably 85 to 105 GPa, more preferably 90 to 105 GPa; and / or a glass-ceramic with a thickness of less than 2.0 mm, and an average light transmittance of 85% or more at a wavelength of 400 to 800 nm, preferably 87% or more, more preferably 88% or more.

[0051] (47) A glass cover containing any of the glass-ceramic articles described in (1) to (23) and / or any of the glass-ceramics described in (24) to (46).

[0052] (48) An electronic device comprising any of the glass-ceramic articles described in (1) to (23), and / or any of the glass-ceramic articles described in (24) to (46), and / or the glass cover described in (47).

[0053] (49) A display device comprising any of the glass-ceramic articles described in (1) to (23), and / or any of the glass-ceramic articles described in (24) to (46), and / or the glass cover plate described in (47).

[0054] The beneficial effects of this invention are: through reasonable component design, the glass ceramics and glass ceramic products obtained by this invention have excellent scratch resistance and light transmittance. Attached Figure Description

[0055] Figure 1 This is the XRD pattern of the glass-ceramic product of Embodiment 1 of the present invention.

[0056] Figure 2 This is a schematic diagram comparing the scratches on the glass-ceramic product and high-alumina glass in Embodiment 1 of this application. Detailed Implementation

[0057] The glass ceramics and glass ceramic articles of the present invention are materials having a crystalline phase (sometimes also called a crystal) and a glassy phase, which are different from amorphous solids. The crystalline phases of the glass ceramics and glass ceramic articles can be identified by the peak angles appearing in the X-ray diffraction patterns of X-ray diffraction analysis.

[0058] Through repeated experiments and research, the inventors of this invention have obtained the glass ceramics and glass ceramic products of this invention by specifying the content and proportion of specific components constituting glass ceramics and glass ceramic products to specific values ​​and causing them to precipitate specific crystalline phases.

[0059] The scope of each component (ingredient) of the matrix glass, glass ceramic, and glass ceramic product of the present invention will be described below. In this specification, unless otherwise specified, the content, total content, and total amount of each component are all expressed as a weight percentage (wt%) relative to the total amount of the matrix glass, glass ceramic, or glass ceramic product in terms of its oxide composition. Here, "oxide composition" refers to the total amount of oxides used as raw materials for the matrix glass, glass ceramic, or glass ceramic product of the present invention, where oxides, complex salts, and hydroxides decompose and transform into oxides upon melting, and the total amount of such oxides is taken as 100%. Furthermore, in this specification, when referred to simply as glass, it refers to the matrix glass before crystallization (i.e., crystallization process treatment); after crystallization (i.e., crystallization process treatment), it is referred to as glass ceramic; and glass ceramic product refers to the product obtained by chemically strengthening glass ceramic.

[0060] Unless otherwise specified in the specific context, the numerical ranges listed herein include upper and lower limits. "Above" and "below" include endpoint values ​​and all integers and fractions within the range, not limited to the specific values ​​listed when the range is defined. The term "and / or" as used herein is inclusive; for example, "A; and / or B" means either only A, or only B, or both A and B.

[0061] In some embodiments of the present invention, the glass-ceramic or glass-ceramic articles contain a spinel crystal phase, preferably zinc aluminum spinel (ZnAl2O4). In some embodiments, it is preferable not to contain a Zn2SiO4 crystal phase to prevent a deterioration in the scratch resistance and drop ball test height of the glass-ceramic and glass-ceramic articles of the present invention.

[0062] In some embodiments, the spinel phase has a higher weight percentage than other phases in the glass-ceramic or glass-ceramic article, preferably zinc-aluminum spinel (ZnAl2O4). In some embodiments, the spinel phase accounts for 20-50% of the weight of the glass-ceramic or glass-ceramic article, preferably 30-50%, and more preferably 30-45%. In some embodiments, the spinel phase constitutes 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50% of the glass-ceramic or glass-ceramic article by weight.

[0063] In some embodiments, the glass ceramics or glass ceramic products of the present invention preferably do not contain spodumene crystal phase and / or zirconia crystal phase. The glass ceramics or glass ceramic products of the present invention can obtain high light transmittance, as well as excellent compressive strength and scratch resistance, and can be used to manufacture cover glass for electronic devices or display devices with high transparency requirements.

[0064] In some embodiments, the glass ceramics or glass ceramic articles of the present invention preferably do not contain quartz crystal phases and / or quartz solid solution crystal phases to prevent a decrease in the light transmittance of the glass ceramics or glass ceramic articles of the present invention.

[0065] SiO2 is a network-forming component of the glass-ceramic and glass-ceramic articles of the present invention. It can improve the chemical stability of the matrix glass, glass-ceramic, and glass-ceramic articles. If the SiO2 content is too low, it is difficult to form glass, and the chemical stability of the glass-ceramic and glass-ceramic articles deteriorates. If the SiO2 content is too high, the viscosity of the glass increases, making it difficult to precipitate crystals during the manufacturing process of glass-ceramic and glass-ceramic articles, and reducing the crystalline phase content of the glass-ceramic and glass-ceramic articles. Therefore, the SiO2 content in the present invention is 43-50%, preferably 44-49%, and more preferably 44-48%. In some embodiments, it may contain 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, and 50% SiO2.

[0066] Al2O3 can improve the scratch resistance of glass ceramics and glass ceramic products. Through extensive experimental research, the inventors discovered that when the Al2O3 content exceeds a certain threshold, highly coordinated aluminum ions are covalently linked to three oxygen atoms. Compared to bridging oxygen atoms with two coordination atoms, this bond type is more ionic, has weaker bond energy, and is more flexible. During energy loading and unloading, these bonds undergo a more efficient bond breaking-closing process. This process locally dissipates mechanical energy, leaving insufficient energy to break the O-Si or O-Al bonds, thus improving the scratch resistance of glass ceramics and glass ceramic products. Furthermore, Al2O3 is also a necessary component for forming the crystalline phase of this invention, improving the mechanical properties of glass ceramics and glass ceramic products. However, excessively high Al2O3 content makes glass melting difficult and requires high melting temperatures. Therefore, the Al2O3 content in this invention is 27.5–35%, preferably 28–34%, and more preferably 28–33%. In some embodiments, it may contain 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, or 35% Al2O3.

[0067] Through extensive experimental research, the inventors discovered that in some embodiments, controlling the ratio of SiO2 content to Al2O3 content (SiO2 / Al2O3) within the range of 1.3 to 1.8 can improve the impact resistance of glass ceramics and glass ceramic products. Therefore, in this invention, a SiO2 / Al2O3 ratio of 1.3 to 1.8 is preferred, a SiO2 / Al2O3 ratio of 1.4 to 1.7 is more preferred, and a SiO2 / Al2O3 ratio of 1.45 to 1.67 is even more preferred. In some implementations, the SiO2 / Al2O3 values ​​are 1.3, 1.31, 1.33, 1.35, 1.37, 1.4, 1.41, 1.43, 1.45, 1.47, 1.5, 1.51, 1.53, 1.55, 1.57, 1.6, 1.61, 1.63, 1.65, 1.67, 1.7, 1.71, 1.73, 1.75, 1.77, and 1.8.

[0068] ZnO can improve the Young's modulus, Vickers hardness, and compressive strength of glass ceramics and glass ceramic products. If the ZnO content is too low, the viscosity of the glass is high, which is not conducive to glass forming; if the ZnO content is higher than 12%, the glass structure is loose, and a large amount of Al2O3 enters the crystals, resulting in poor scratch resistance of glass ceramics and glass ceramic products, with scratch widths of more than 30 μm. At the same time, crystallization easily occurs on the surface during glass forming, and white spots are generated inside. Therefore, the ZnO content in this invention is 8.5-12%, preferably 9-12%, and more preferably 9-11%. In some embodiments, it may contain 8.5%, 8.7%, 9%, 9.3%, 9.5%, 9.7%, 10%, 10.3%, 10.5%, 10.7%, 11%, 11.3%, 11.5%, 11.7%, or 12% ZnO.

[0069] MgO helps reduce the viscosity of glass, refines grains during crystallization, and improves the transmittance of glass ceramics and glass ceramic products. However, if the MgO content is too high, severe surface crystallization occurs during glass crystallization, resulting in a decrease in the transmittance of glass ceramics and glass ceramic products. Therefore, the MgO content in this invention is 0-5%, preferably 1-4%, and more preferably 1-3%. In some embodiments, it may contain 0%, greater than 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2 ... MgO concentrations of 0.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, and 5%.

[0070] Through extensive experimental research, the inventors discovered that in some embodiments, controlling the ratio of the total content of ZnO, MgO, and SiO2 (ZnO+MgO+SiO2) to the content of Al2O3 (ZnO+MgO+SiO2) / Al2O3 within the range of 1.5 to 2.15 is beneficial to improving the scratch resistance of glass ceramics and glass ceramic products. Therefore, it is preferable that the ratio of (ZnO+MgO+SiO2) / Al2O3 is 1.5 to 2.15, more preferably 1.6 to 2.15, and even more preferably 1.8 to 2.1. In some implementations, the value of (ZnO+MgO+SiO2) / Al2O3 is 1.5, 1.53, 1.55, 1.57, 1.6, 1.63, 1.65, 1.67, 1.7, 1.73, 1.75, 1.77, 1.8, 1.83, 1.85, 1.87, 1.9, 1.93, 1.95, 1.97, 2.0, 2.01, 2.02, 2.03, 2.04, 2.05, 2.06, 2.07, 2.08, 2.09, 2.1, 2.11, 2.12, 2.13, 2.14, or 2.15.

[0071] Li₂O can reduce the viscosity and melting temperature of glass, and also participates in chemical strengthening, increasing the surface stress and drop ball test height of glass-ceramic products. However, if the Li₂O content is too high, it easily forms a quartz solid solution phase, reducing the transmittance of the glass-ceramic products. Therefore, the Li₂O content in this invention is 0.1–5%, preferably 1–5%, and more preferably 1–4%. In some embodiments, it may contain 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% Li₂O.

[0072] In some embodiments, controlling the Al2O3 / Li2O ratio (Al2O3 / Li2O) within the range of 11.0 to 60.0 is beneficial for increasing the drop ball test height of glass ceramics and glass ceramic products, and improving their compressive strength. Therefore, an Al2O3 / Li2O ratio of 11.0 to 60.0 is preferred, 12.0 to 40.0 is more preferred, and 13.0 to 20.0 is even more preferred. In some implementations, the Al2O3 / Li2O value is 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 25.0, 26.0, 2 7.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, 54.0, 55.0, 56.0, 57.0, 58.0, 59.0, 60.0.

[0073] The role of Na₂O is to promote glass melting and improve the chemical strengthening properties of glass. However, excessive Na₂O can lead to more broken bonds in the glass, reducing the strength of the matrix glass and negatively impacting the strength of glass ceramics and glass ceramic products. Therefore, the Na₂O content in this invention is 0-7%, preferably 1-6%, and more preferably 2-5%. In some embodiments, it may contain 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%. 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.5%, 7% Na2O.

[0074] In some embodiments, controlling the ratio (ZnO+MgO) / (Li2O+Na2O) between the total content of ZnO and MgO (ZnO+MgO) and the total content of Li2O and Na2O (Li2O+Na2O) to be in the range of 1.5 to 5.0 is beneficial to improving the extrusion strength and drop ball test height of the glass ceramic and glass ceramic products of the present invention. Therefore, it is preferable that (ZnO+MgO) / (Li2O+Na2O) is 1.5 to 5.0, more preferably (ZnO+MgO) / (Li2O+Na2O) is 1.7 to 4.5, and even more preferably (ZnO+MgO) / (Li2O+Na2O) is 1.8 to 4.0. In some embodiments, the value of (ZnO+MgO) / (Li2O+Na2O) is 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.

[0075] TiO2 and ZrO2 are nucleating agents for the glass ceramics and glass ceramic products of this invention. The simultaneous use of these two nucleating agents can maximize the number of crystal nuclei in the glass ceramics and glass ceramic products, resulting in more nuclei, more stable crystal phase growth, and more uniform crystal size. If the TiO2 content is too high, it will lead to severe coloring (brownish-yellow) in the glass ceramics and glass ceramic products, reducing their transmittance in the visible light region. If the ZrO2 content is too high, the melting of the glass becomes more difficult. Therefore, the TiO2 content in this invention is 2-6%, preferably 2-5%, more preferably 2-4%. The ZrO2 content is 0-5%, preferably 0.5-4%, more preferably 1-3%. In some embodiments, it may contain 2%, 2.1%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, or 6% TiO2. In some implementations, the percentages may include 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, etc. 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, and 5% ZrO2.

[0076] In some embodiments, controlling the ratio (TiO2+ZrO2) / (Li2O+Na2O) between the total content of TiO2 and ZrO2 (TiO2+ZrO2) and the total content of Li2O and Na2O (Li2O+Na2O) in the range of 0.5 to 5.0 is beneficial to improving the light transmittance of glass ceramics and glass ceramic products. Therefore, it is preferable that (TiO2+ZrO2) / (Li2O+Na2O) is 0.5 to 5.0, more preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 3.0, and even more preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 1.5. In some implementations, the value of (TiO2+ZrO2) / (Li2O+Na2O) is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.

[0077] K₂O helps lower the melting temperature of glass, which is beneficial for chemical strengthening and can increase the depth of the ion exchange layer in glass ceramics and glass ceramic products. However, if the K₂O content is too high, it can easily lead to a decrease in the chemical stability and mechanical strength of the glass. Therefore, the K₂O content in this invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, K2O may be included in amounts of 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, and 3%.

[0078] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3) can improve the structural density and scratch resistance of glass ceramics and glass ceramic products. However, excessive content can lead to difficulties in crystal formation during the crystallization process of glass ceramics and glass ceramic products, a decrease in the crystalline phase content, and a decrease in the drop ball test height. Therefore, the content of Ln2O3 in this invention is 0-8%, preferably 0.1-6%, and more preferably 0.1-3%. In some implementations, the percentages may include 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, etc. 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8% of Ln2O3.

[0079] In some embodiments, controlling the ratio (Al2O3+Ln2O3) / Li2O between the total content of Al2O3 and Ln2O3 (Ln2O3+TiO2) and the content of Li2O (Al2O3+Ln2O3) / Li2O in the range of 14.5 to 100.0 is beneficial to improving the scratch resistance of glass ceramics and glass ceramic products. Therefore, it is preferable that (Al2O3+Ln2O3) / Li2O is 14.5 to 100.0, more preferably (Al2O3+Ln2O3) / Li2O is 15.0 to 60.0, and even more preferably (Al2O3+Ln2O3) / Li2O is 16.0 to 40.0. In some implementations, the value of (Al₂O₃+Ln₂O₃) / Li₂O is 14.5, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0, 21.0, 22.0, 23.0, 24.0, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, or 54. 0, 55.0, 56.0, 57.0, 58.0, 59.0, 60.0, 61.0, 62.0, 63.0, 64.0, 65.0, 66.0, 67.0, 68.0, 69.0, 70.0, 71.0, 72.0, 73.0, 74.0, 75.0, 76.0, 77.0, 78.0, 79.0, 80.0, 81.0, 82.0, 83.0, 84.0, 85.0, 86.0, 87.0, 88.0, 89.0, 90.0, 91.0, 92.0, 93.0, 94.0, 95.0, 96.0, 97.0, 98.0, 99.0, 100.0.

[0080] B2O3 is used as a flux to aid in the melting of glass. However, if the B2O3 content is too high, the chemical stability of the glass ceramic and glass ceramic products will deteriorate. In addition, boron volatilization can easily form streaks, causing inhomogeneity within the glass ceramic and glass ceramic products. Therefore, the B2O3 content is 0-4%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is even more preferable that the glass ceramic does not contain B2O3. In some embodiments, the composition may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, and 4% B2O3.

[0081] CaO, BaO, and SrO do not participate in crystal phase formation and remain in the residual glass phase of glass ceramics and glass ceramic products. This is beneficial for lowering the melting and processing temperatures. However, excessively high content can impair nucleation and crystallization during the transformation of the matrix glass into glass ceramics, adversely affecting the chemical stability of glass ceramics and glass ceramic products. Therefore, the total content of CaO, BaO, and SrO (CaO+BaO+SrO) is 0-5%, preferably 0-4%, and more preferably 0-2%. In some embodiments, the content of CaO+BaO+SrO is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, and 2.1%. %, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%.

[0082] In some embodiments, the matrix glass, glass ceramic, or glass ceramic product may also contain 0-2% clarifying agent to improve the defoaming ability of the matrix glass, glass ceramic, or glass ceramic product. Such clarifying agent includes, but is not limited to, one or more of Sb₂O₃, SnO₂, SnO, CeO₂, F (fluorine) compounds, Cl (chlorine) compounds, and Br (bromine) compounds, with Sb₂O₃ being preferred. In some embodiments, it is preferable to omit SnO₂ and / or SnO, which is beneficial for the precipitation of spinel crystal phases in the glass ceramic and glass ceramic product of the present invention, especially the formation of ZnAl₂O₄ crystal phases, ensuring the acquisition of the desired crystal phase type, preventing the formation of spodumene and zirconia crystal phases, and improving the compressive strength and scratch resistance of the glass ceramic and glass ceramic product. When the above-mentioned clarifying agents are present alone or in combination, the upper limit of their content is preferably 2%, more preferably 1%, and even more preferably 0.5%. In some embodiments, the content of one or more clarifying agents is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2%.

[0083] Without affecting the performance of the matrix glass, glass ceramic, or glass ceramic product of the present invention, other components not mentioned above, such as Nb2O5, WO3, Bi2O3, Ta2O5, and TeO2, may be appropriately included. However, to maintain the excellent performance of the matrix glass, glass ceramic, or glass ceramic product of the present invention, the content of each of Nb2O5, WO3, Bi2O3, Ta2O5, and TeO2, or their combined content, is preferably 5% or less, more preferably 2% or less, further preferably 1% or less, and even more preferably not included.

[0084] In some embodiments, the matrix glass, glass ceramic, and glass ceramic products of the present invention preferably do not contain P2O5. The glass ceramic or glass ceramic products of the present invention can obtain better scratch resistance and can be used to manufacture cover glass for electronic devices or display devices with high scratch resistance requirements.

[0085] PbO and As2O3 are toxic substances, and even small amounts do not meet environmental protection requirements. Therefore, in some embodiments of the present invention, it is preferable that PbO and / or As2O3 are not present.

[0086] The terms "not containing" and "0%" as used herein mean that the compound, molecule, or element was not intentionally added as a raw material to the matrix glass, glass ceramic, or glass ceramic product of this invention. However, as raw materials and / or equipment used in the production of matrix glass, glass ceramic, or glass ceramic product, there may be certain impurities or components that are not intentionally added, which may be present in small or trace amounts in the final matrix glass, glass ceramic, or glass ceramic product. Such cases are also within the scope of protection of this patent.

[0087] The grain size and crystal phase type of the glass-ceramic or glass-ceramic product of the present invention affect the light transmittance of the glass-ceramic or glass-ceramic product; the smaller the grain size, the higher the light transmittance. In some embodiments, the glass-ceramic or glass-ceramic product of the present invention exhibits high transparency in the visible light range. Regarding the high transmittance of the glass-ceramic or glass-ceramic product in the visible light range, in some embodiments, the average light transmittance of the glass-ceramic product with a thickness of 2.0 mm or less, or the glass-ceramic product at 400–800 nm, is preferably 85% or more, more preferably 87% or more, and even more preferably 88% or more.

[0088] The matrix glass, glass ceramic, and glass ceramic articles of the present invention can be produced and manufactured by the following methods:

[0089] Forming the matrix glass: Raw materials (oxides, hydroxides, complex salts, boric acid, etc.) are mixed uniformly according to the component ratio. The uniform mixture is placed in a crucible (e.g., a platinum or quartz crucible). Depending on the melting ease of the glass composition, melting is carried out in an electric or gas furnace at a temperature range of 1500–1700°C for 5–24 hours, preferably at 1500–1600°C. The matrix glass is then obtained after clarification, homogenization, shaping, and annealing. The clarification temperature is preferably 1550–1650°C, and the annealing temperature is preferably 550–650°C.

[0090] The matrix glass of the present invention can be formed by well-known methods.

[0091] The matrix glass of this invention undergoes a crystallization process after molding or processing, resulting in uniform crystal precipitation within the glass to form a glass-ceramic. This crystallization process can be performed in one stage or two stages, preferably in two stages. The two-stage crystallization process involves a nucleation process at a first temperature followed by a crystal growth process at a second temperature. The crystallization process performed at the first temperature is referred to as the first crystallization process, and the crystallization process performed at the second temperature is referred to as the second crystallization process.

[0092] To achieve the desired physicochemical properties in glass-ceramics, the preferred crystallization process is as follows:

[0093] The crystallization process described above, performed in a single stage, allows for continuous nucleation and crystal growth. Specifically, the temperature is raised to a predetermined crystallization temperature, maintained for a certain period, and then cooled. The preferred crystallization temperature is 600–800°C, but more preferably 650–750°C to precipitate the desired crystalline phase. The holding time at the crystallization temperature is preferably 1–10 hours, more preferably 3–6 hours.

[0094] When the crystallization process is carried out in two stages, the first temperature is preferably 600-700°C, the second temperature is preferably greater than 750°C but less than or equal to 900°C, the holding time at the first temperature is preferably 1-6 hours, and the holding time at the second temperature is preferably 2-5 hours.

[0095] In some embodiments, the matrix glass or glass-ceramic described herein can be manufactured into shaped bodies using various processes, including but not limited to sheets, and the processes include but not limited to slot drawing, float glass, roll forming, and other sheet forming processes known in the art. Alternatively, the matrix glass or glass-ceramic can be formed using float glass or roll forming methods known in the art. The shaped bodies described in this invention also include lenses, prisms, etc.

[0096] The matrix glass or glass-ceramic of the present invention can be manufactured into sheet glass or glass-ceramic bodies by methods such as grinding or polishing, but the method of manufacturing glass or glass-ceramic bodies is not limited to these methods.

[0097] The matrix glass or glass-ceramic of the present invention can be prepared into various shapes of glass molded bodies or glass-ceramic molded bodies by means of hot bending or molding processes at a certain temperature, but is not limited to these methods.

[0098] In some embodiments, a hot bending process can be used to produce glass or glass-ceramic molded bodies. The hot bending process involves placing 2D or 2.5D glass or glass-ceramic in a mold and sequentially performing steps such as heating and preheating, pressing and forming, and holding and cooling in a hot bending machine to obtain a 3D curved glass or glass-ceramic molded body.

[0099] In some embodiments, the glass-ceramic molded body has a 2.5D or 3D structure, i.e., the glass-ceramic molded body has a non-planar structure. As used herein, "non-planar structure" means that in a 2.5D or 3D shape, at least a portion of the glass-ceramic molded body extends outward or along an angle with a plane defined by the original, layout configuration of the 2D matrix glass. The 2.5D or 3D glass-ceramic molded body formed from the matrix glass may have one or more protrusions or curved portions.

[0100] The matrix glass, glass ceramics, and glass ceramic articles described in this invention can have any reasonably useful thickness.

[0101] In addition to improving mechanical properties through precipitation crystallization, the glass ceramics of the present invention can also obtain superior mechanical properties by forming a compressive stress layer, thereby producing glass ceramic products.

[0102] In some embodiments, the substrate glass or glass ceramic can be processed into sheets and / or shaped (such as drilling, hot bending, etc.), polished and / or swept after shaping, and then chemically strengthened through a chemical strengthening process.

[0103] The chemical strengthening method described in this invention includes ion exchange. During ion exchange, smaller metal ions in the matrix glass or glass-ceramic are replaced or "exchanged" by larger metal ions of the same valence state located nearby in the matrix glass or glass-ceramic. Replacing smaller ions with larger ions creates compressive stress in the matrix glass or glass-ceramic, forming a compressive stress layer.

[0104] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na+). + K + 、Rb + Cs + Ion exchange is carried out by immersing a matrix glass or glass-ceramic in a salt bath containing at least one molten salt containing larger metal ions, which replace smaller metal ions in the matrix glass. One or more ion exchange processes used to chemically strengthen a matrix glass or glass-ceramic may include, but are not limited to, immersion in a single salt bath, or immersion in multiple salt baths having the same or different compositions, with washing and / or annealing steps between immersions.

[0105] In some embodiments, the matrix glass or glass-ceramic can be ion-exchanged by immersion in a salt bath of molten Na salt (such as NaNO3) at a temperature of about 350–470°C for about 1–36 hours, preferably at a temperature range of 400–460°C, and preferably for a time range of 2–15 hours. In this embodiment, Na ions replace some of the Li ions in the matrix glass or glass-ceramic, thereby forming a surface compression layer and exhibiting high mechanical properties. In some embodiments, the matrix glass or glass-ceramic can be ion-exchanged by immersion in a mixed salt bath of molten K salt and Na salt at a temperature of about 360–460°C for 1–36 hours, preferably for a time range of 2–24 hours.

[0106] The glass-ceramic of this invention possesses highly efficient low-temperature ion exchange properties. In some embodiments, at relatively low ion exchange temperatures and short exchange times, the surface stress of the glass-ceramic product can reach over 40 MPa. After ion exchange, the hardness of the glass-ceramic product is significantly improved, mainly because ion exchange, through a "squeezing effect," creates high compressive stress on the surface of the glass-ceramic product, thereby increasing its resistance to deformation and improving its hardness. In some embodiments, after chemical strengthening, the glass-ceramic product of this invention can achieve a Vickers hardness of up to 600 kgf / mm². 2 above.

[0107] The glass-ceramic products of the present invention exhibit excellent scratch resistance. In some embodiments, after chemical strengthening, the glass-ceramic products of the present invention have scratch widths of less than 30 μm.

[0108] The performance indicators of the glass ceramics and / or glass ceramic products of this invention are tested using the following methods:

[0109] [Grain Size]

[0110] The size of the grains was determined by surface treatment with HF acid followed by gold sputtering. The surface was then scanned under a scanning electron microscope.

[0111] [Light transmittance]

[0112] The light transmittance mentioned in this article refers to external transmittance, sometimes simply referred to as transmittance.

[0113] The sample was processed to a thickness of less than 2 mm and the opposite surfaces were polished in parallel. The average light transmittance of 400-800 nm was measured using a Hitachi U-41000 spectrophotometer.

[0114] [Surface Stress (CS)]

[0115] Surface stress was measured using a glass surface stress meter SLP-2000.

[0116] The measurement conditions were calculated with the sample's refractive index being 1.57 and its optical elastic constant being 28 [(nm / cm) / MPa].

[0117] [Scratch resistance]

[0118] The scratch resistance of this invention is characterized by scratch width using a Knoop microindentation hardness tester with a tapered Knoop indenter. A 145mm × 67mm × 0.7mm sample is placed on a stage and fixed. A fixed load of 8 N is applied to the indenter, and the indenter is used to etch a predetermined distance across the sample surface at a predetermined speed. The scratch width is observed under a microscope. The scratch resistance of the sample is determined based on the scratch width; the wider the scratch, the worse the scratch resistance.

[0119] [Drop resistance]

[0120] Drop resistance testing was conducted using a WH-2101 drop tester. Two glass products of the same specifications (each weighing 20g, load two pieces) were loaded onto a 2D sample. 80-grit sandpaper was placed on a base, and the sample (145mm × 67mm × 0.7mm) was dropped freely from a specified height onto the sandpaper. The drop resistance was measured from the height from which the sample could withstand an impact without breaking. Specifically, the test started at a height of 600mm, and the heights were increased sequentially to 700mm, 800mm, 900mm, 1000mm, and above without breakage. For the embodiment demonstrating "drop resistance," glass-ceramic products were used as the test object. In this embodiment, test data recorded at 1000mm indicates that the glass-ceramic product withstood the impact without breaking even when loaded from a height of 1000mm. The maximum test height for the WH-2101 drop tester was 2000mm.

[0121] [Drop test height]

[0122] A 145mm × 67mm × 0.7mm sample is placed on a glass bearing fixture, and a 132g steel ball is dropped from a specified height, with the impact point being the center of the sample. This is the maximum drop ball test height from which the sample can withstand the impact without breaking. Specifically, the drop ball test height starts at 400mm, with each drop occurring once at each height. If the sample does not break, the height is increased by 100mm each time, and the test continues until the sample breaks. In the embodiment with a "drop ball test height," glass-ceramic products are used as the test object. In this embodiment, the test data is recorded as 1700mm, indicating that the glass-ceramic product withstood the impact without breaking even when a steel ball is dropped from a height of 1700mm. In this invention, the drop ball test height is sometimes simply referred to as the drop ball height.

[0123] Vickers hardness

[0124] The load (N) when a diamond pyramid indenter with a 136° angle between its two faces is used to press a pyramid-shaped indentation into the test surface is divided by the surface area (mm) calculated from the length of the indentation. 2The value is represented by ). The test is conducted with a load of 100 (N) and a holding time of 15 (seconds). In this invention, Vickers hardness is sometimes simply referred to as hardness.

[0125] [Compressive strength]

[0126] A CMT6502 microcomputer-controlled electronic universal testing machine was used. A 145mm × 67mm × 0.7mm sample was placed on a glass support fixture. The compression rod had a mushroom-head design with a diameter of ¢10mm, and the compression speed was 5mm / min until the sample broke. Calibration with a fixture was required before testing, and the test point was at the center. The test button was pressed until the sample broke under pressure, and the pressure (N) at break was recorded. For the embodiment with "compression strength," a glass-ceramic product was used as the test object. In this embodiment, a test data of 500N was recorded, indicating that the maximum compressive force the glass-ceramic product could withstand before breaking was 500N.

[0127] Young's modulus

[0128] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.

[0129]

[0130] G = V S 2 ρ

[0131] In the formula: E is Young's modulus, Pa;

[0132] G is the shear modulus, Pa;

[0133] V T The transverse wave velocity is in m / s;

[0134] V S The longitudinal wave velocity is given in m / s.

[0135] ρ is the density of glass, in g / cm³ 3 .

[0136] The glass-ceramic products of the present invention have the following properties:

[0137] 1) In some embodiments, the grain size of the glass-ceramic article is less than 70 nm, preferably less than 60 nm, more preferably less than 50 nm, and even more preferably less than 48 nm.

[0138] 2) In some embodiments, the surface stress (CS) of the glass-ceramic article is 40 MPa or more, preferably 80 to 200 MPa, and more preferably 100 to 200 MPa.

[0139] 3) In some embodiments, the drop ball test height of the glass-ceramic product is 800 mm or more, preferably 1000 mm or more, and more preferably 1200 mm or more.

[0140] 4) In some embodiments, the impact resistance of the glass-ceramic product is 800 mm or more, preferably 1000 mm or more, and more preferably 1200 mm or more.

[0141] 5) In some embodiments, the compressive strength of the glass-ceramic product is 200N or more, preferably 250N or more, and more preferably 300N or more.

[0142] 6) In some embodiments, the Young's modulus (E) of the glass-ceramic article is 80-105 GPa, preferably 85-105 GPa, and more preferably 90-105 GPa.

[0143] 7) In some embodiments, the scratch width of the glass-ceramic article is less than 30 μm, preferably less than 25 μm, and more preferably less than 20 μm.

[0144] 8) In some embodiments, the Vickers hardness (H) of the glass-ceramic article v ) is 600 kgf / mm 2 The above values ​​are preferably 650–800 kgf / mm². 2 More preferably, it is 680–800 kgf / mm 2 .

[0145] 9) In some embodiments, the glass-ceramic article with a thickness of 2.0 mm or less has an average light transmittance of 85% or more at a wavelength of 400-800 nm, preferably 87% or more, more preferably 88% or more. The thickness is preferably 0.2-2.0 mm, more preferably 0.3-1.0 mm, and even more preferably 0.5-1.0 mm.

[0146] The glass-ceramic of the present invention has the following properties:

[0147] 1) In some embodiments, the grain size of the glass ceramic is 70 nm or less, preferably 60 nm or less, more preferably less than 50 nm, and even more preferably 48 nm or less.

[0148] 2) In some embodiments, the glass-ceramic with a thickness of 2.0 mm or less has an average light transmittance of 85% or more at a wavelength of 400-800 nm, preferably 87% or more, and more preferably 88% or more. The thickness is preferably 0.2-2.0 mm, more preferably 0.3-1.0 mm, and even more preferably 0.5-1.0 mm.

[0149] 3) In some embodiments, the Vickers hardness (H) of the glass-ceramic is...v ) is 500 kgf / mm 2 The above values ​​are preferably 600–750 kgf / mm². 2 More preferably, it is 650–750 kgf / mm 2 .

[0150] 4) In some embodiments, the Young's modulus (E) of the glass ceramic is 80 to 105 GPa, preferably 85 to 105 GPa, and more preferably 90 to 105 GPa.

[0151] The glass ceramics, glass ceramic products, and matrix glass of this invention, due to their superior properties, can be widely used to manufacture glass covers or glass components. Furthermore, the glass ceramics, glass ceramic products, and matrix glass of this invention can be applied to electronic devices or display devices, such as mobile phones, watches, computers, and touch screens. They can be used to manufacture protective glass for mobile phones, smartphones, tablets, laptops, PDAs, televisions, personal computers, MTA machines, or industrial displays; or to manufacture touch screens, protective windows, car windows, train windows, aircraft mechanical windows, and touch screen protective glass; or to manufacture hard drive substrates or solar cell substrates; or to manufacture white goods, such as refrigerator components or kitchenware.

[0152] Example

[0153] To further clarify and illustrate the technical solution of the present invention, the following non-limiting embodiments are provided. While considerable effort has been made to ensure the accuracy of the numerical values ​​in these embodiments, some errors and deviations must be considered. The composition itself is given based on oxides in weight percent and has been normalized to 100%.

[0154] <Examples of Glass-Ceramic Technology>

[0155] In this embodiment, glass ceramics with the compositions shown in Tables 1 to 3 were obtained using the glass ceramic manufacturing method described above. Furthermore, the characteristics of each glass ceramic were measured using the testing method described in this invention, and the measurement results are shown in Tables 1 to 3. In the following examples, the average light transmittance test sample thickness for wavelengths of 400–800 nm was 1 mm.

[0156] Table 1.

[0157]

[0158]

[0159] Table 2.

[0160]

[0161]

[0162] Table 3.

[0163]

[0164]

[0165] <Examples of Glass-Ceramic Products>

[0166] This embodiment uses the above-described manufacturing method for glass-ceramic products to obtain glass-ceramic products with the compositions shown in Tables 4 to 6. Furthermore, the characteristics of each glass-ceramic product were measured using the testing method described in this invention, and the measurement results are shown in Tables 4 to 6. In the following embodiments, the average light transmittance test sample thickness for wavelengths of 400–800 nm was 1.0 mm.

[0167] Table 4.

[0168]

[0169]

[0170] Table 5.

[0171]

[0172]

[0173] Table 6.

[0174]

[0175]

[0176] The glass-ceramic products prepared according to the embodiments of the present invention were tested:

[0177] The crystal phase was tested using X-ray diffraction (XRD). Figure 1 This is the XRD pattern of the glass-ceramic product of Example 1 of this application. As can be seen from the XRD pattern, the crystal phase is zinc spinel (ZnAl2O4).

[0178] The scratch resistance of glass-ceramic products was tested using a Knoop microindentation hardness tester. Figure 2 This is a comparative schematic diagram of scratches on the glass-ceramic product of Embodiment 1 of this application and high-alumina glass. The scratch width of the glass-ceramic product in Embodiment 1 is 9 μm, while the scratch width of the high-alumina glass is much greater than 9 μm, and the edge chipping is severe. Figure 2 It can be seen that the glass-ceramic products of the present invention have a small scratch width and excellent scratch resistance.

Claims

1. A glass-ceramic product, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 43–50%; Al2O3: 27.5–35%; ZnO: 8.5–12%; Li2O: 0.1–5%; TiO2: 2–6%.

2. The glass-ceramic product according to claim 1, characterized in that, Its components, expressed as a percentage by weight, also contain: MgO: 0–5%; and / or Na2O: 0–7%; and / or ZrO2: 0–5%; and / or K2O: 0–3%; and / or B2O3: 0–4%; and / or CaO+BaO+SrO: 0–5%; and / or Ln2O3: 0–8%; and / or clarifying agent: 0–2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

3. A glass-ceramic product, characterized in that, Its composition, expressed as a weight percentage, is as follows: SiO2: 43–50%; Al2O3: 27.5–35%; ZnO: 8.5–12%; Li2O: 0.1–5%. TiO2: 2-6%; The composition includes: MgO: 0-5%; Na2O: 0-7%; ZrO2: 0-5%; K2O: 0-3%; B2O3: 0-4%; CaO+BaO+SrO: 0-5%; Ln2O3: 0-8%; and clarifying agent: 0-2%. The Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

4. The glass-ceramic product according to any one of claims 1 to 3, characterized in that, Its components are expressed as a weight percentage, wherein: (ZnO+MgO+SiO2) / Al2O3 is 1.5 to 2.15, preferably (ZnO+MgO+SiO2) / Al2O3 is 1.6 to 2.15, and more preferably (ZnO+MgO+SiO2) / Al2O3 is 1.8 to 2.

1.

5. The glass-ceramic product according to any one of claims 1 to 3, characterized in that, Its components are expressed as a weight percentage, wherein: Al2O3 / Li2O is 11.0 to 60.0, preferably Al2O3 / Li2O is 12.0 to 40.0, and more preferably Al2O3 / Li2O is 13.0 to 20.

0.

6. The glass-ceramic product according to any one of claims 1 to 3, characterized in that, Its components are expressed as a weight percentage, wherein: (ZnO+MgO) / (Li2O+Na2O) is 1.5 to 5.0, preferably (ZnO+MgO) / (Li2O+Na2O) is 1.7 to 4.5, and more preferably (ZnO+MgO) / (Li2O+Na2O) is 1.8 to 4.

0.

7. The glass-ceramic product according to any one of claims 1 to 3, characterized in that, Its components are expressed as a weight percentage, wherein: (TiO2+ZrO2) / (Li2O+Na2O) is 0.5 to 5.0, preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 3.0, and more preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 1.

5.

8. The glass-ceramic article according to any one of claims 1 to 3, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Al2O3 is 1.3 to 1.8, preferably 1.4 to 1.7, and more preferably 1.45 to 1.

67.

9. The glass-ceramic product according to any one of claims 1 to 3, characterized in that, Its components are expressed as a weight percentage, wherein: (Al2O3+Ln2O3) / Li2O is 14.5 to 100.0, preferably (Al2O3+Ln2O3) / Li2O is 15.0 to 60.0, more preferably (Al2O3+Ln2O3) / Li2O is 16.0 to 40.0, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

10. The glass-ceramic article according to any one of claims 1 to 3, characterized in that, Its components are expressed as weight percentages, wherein: SiO2: 44-49%, preferably SiO2: 44-48%; and / or Al2O3: 28-34%, preferably Al2O3: 28-33%; and / or Li2O: 1-5%, preferably Li2O: 1-4%; and / or ZnO: 9-12%, preferably ZnO: 9-11%; and / or TiO2: 2-5%, preferably TiO2: 2-4%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or Ln2O3: 0.1-6%, preferably Ln2O3: 0.1-3%; And / or ZrO2: 0.5-4%, preferably ZrO2: 1-3%; and / or Na2O: 1-6%, preferably Na2O: 2-5%; and / or MgO: 1-4%, preferably MgO: 1-3%; and / or B2O3: 0-2%, preferably B2O3: 0-1%; and / or CaO+BaO+SrO: 0-4%, preferably CaO+BaO+SrO: 0-2%; and / or clarifying agent: 0-1%, preferably clarifying agent: 0-0.5%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

11. The glass-ceramic article according to claim 1 or 2, characterized in that, Its components, expressed as a weight percentage, contain: Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%, more preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%, and even more preferably does not contain Nb2O5, and / or does not contain WO3, and / or does not contain Bi2O3, and / or does not contain Ta2O5, and / or does not contain TeO2.

12. The glass-ceramic product according to any one of claims 1 to 3, characterized in that, The glass-ceramic product does not contain P2O5, and / or does not contain B2O3, and / or does not contain SnO2, and / or does not contain SnO.

13. The glass-ceramic article according to any one of claims 1 to 3, characterized in that, The glass-ceramic product contains a spinel crystal phase, preferably with a higher weight percentage than other crystal phases, more preferably with the spinel crystal phase accounting for 20-50% of the weight of the glass-ceramic product, even more preferably with the spinel crystal phase accounting for 30-50% of the weight of the glass-ceramic product, and even more preferably with the spinel crystal phase accounting for 30-45% of the weight of the glass-ceramic product.

14. The glass-ceramic article according to claim 13, characterized in that, The spinel crystal phase is ZnAl2O4.

15. The glass-ceramic article according to any one of claims 1 to 3, characterized in that, The glass-ceramic product does not contain spodumene crystal phase, and / or does not contain zirconium oxide crystal phase, and / or does not contain quartz crystal phase, and / or does not contain quartz solid solution crystal phase, and / or does not contain Zn2SiO4 crystal phase.

16. The glass-ceramic article according to any one of claims 1 to 3, characterized in that, The glass-ceramic product has a grain size of less than 70 nm, preferably less than 60 nm, more preferably less than 50 nm, and even more preferably less than 48 nm; and / or a surface stress of 40 MPa or more, preferably 80-200 MPa, more preferably 100-200 MPa; and / or a drop ball test height of 800 mm or more, preferably 1000 mm or more, more preferably 1200 mm or more; and / or a drop resistance of 800 mm or more, preferably 1000 mm or more, more preferably 1200 mm or more; and / or a compressive strength of 200 N or more, preferably 250 N or more, more preferably 300 N or more; and / or a Young's modulus E of 80-105 GPa, preferably 85-105 GPa, more preferably 90-105 GPa; and / or a scratch width of less than 30 μm, preferably less than 25 μm, more preferably less than 20 μm; and / or a Vickers hardness of 600 kgf / mm². 2 The above values ​​are preferably 650–800 kgf / mm². 2 More preferably, it is 680–800 kgf / mm 2 ; and / or glass-ceramic products with a thickness of less than 2.0 mm, having an average light transmittance of 85% or more at a wavelength of 400 to 800 nm, preferably 87% or more, and more preferably 88% or more.

17. A glass-ceramic material, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 43–50%; Al2O3: 27.5–35%; ZnO: 8.5–12%; Li2O: 0.1–5%; TiO2: 2–6%.

18. The glass-ceramic according to claim 17, characterized in that, Its components, expressed as a percentage by weight, also contain: MgO: 0–5%; and / or Na2O: 0–7%; and / or ZrO2: 0–5%; and / or K2O: 0–3%; and / or B2O3: 0–4%; and / or CaO+BaO+SrO: 0–5%; and / or Ln2O3: 0–8%; and / or clarifying agent: 0–2%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

19. A glass-ceramic material, characterized in that, Its composition, expressed as a weight percentage, is as follows: SiO2: 43–50%; Al2O3: 27.5–35%; ZnO: 8.5–12%; Li2O: 0.1–5%. TiO2: 2-6%; The composition includes: MgO: 0-5%; Na2O: 0-7%; ZrO2: 0-5%; K2O: 0-3%; B2O3: 0-4%; CaO+BaO+SrO: 0-5%; Ln2O3: 0-8%; and clarifying agent: 0-2%. The Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

20. The glass-ceramic according to any one of claims 17 to 19, characterized in that, Its components are expressed as a weight percentage, wherein: (ZnO+MgO+SiO2) / Al2O3 is 1.5 to 2.15, preferably (ZnO+MgO+SiO2) / Al2O3 is 1.6 to 2.15, and more preferably (ZnO+MgO+SiO2) / Al2O3 is 1.8 to 2.

1.

21. The glass-ceramic according to any one of claims 17 to 19, characterized in that, Its components are expressed as a weight percentage, wherein: Al2O3 / Li2O is 11.0 to 60.0, preferably Al2O3 / Li2O is 12.0 to 40.0, and more preferably Al2O3 / Li2O is 13.0 to 20.

0.

22. The glass-ceramic according to any one of claims 17 to 19, characterized in that, Its components are expressed as a weight percentage, wherein: (ZnO+MgO) / (Li2O+Na2O) is 1.5 to 5.0, preferably (ZnO+MgO) / (Li2O+Na2O) is 1.7 to 4.5, and more preferably (ZnO+MgO) / (Li2O+Na2O) is 1.8 to 4.

0.

23. The glass-ceramic according to any one of claims 17 to 19, characterized in that, Its components are expressed as a weight percentage, wherein: (TiO2+ZrO2) / (Li2O+Na2O) is 0.5 to 5.0, preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 3.0, and more preferably (TiO2+ZrO2) / (Li2O+Na2O) is 0.7 to 1.

5.

24. The glass-ceramic according to any one of claims 17 to 19, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Al2O3 is 1.3 to 1.8, preferably 1.4 to 1.7, and more preferably 1.45 to 1.

67.

25. The glass-ceramic according to any one of claims 17 to 19, characterized in that, Its components are expressed as a weight percentage, wherein: (Al2O3+Ln2O3) / Li2O is 14.5 to 100.0, preferably (Al2O3+Ln2O3) / Li2O is 15.0 to 60.0, more preferably (Al2O3+Ln2O3) / Li2O is 16.0 to 40.0, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

26. The glass-ceramic according to any one of claims 17 to 19, characterized in that, Its components are expressed as weight percentages, wherein: SiO2: 44-49%, preferably SiO2: 44-48%; and / or Al2O3: 28-34%, preferably Al2O3: 28-33%; and / or Li2O: 1-5%, preferably Li2O: 1-4%; and / or ZnO: 9-12%, preferably ZnO: 9-11%; and / or TiO2: 2-5%, preferably TiO2: 2-4%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or Ln2O3: 0.1-6%, preferably Ln2O3: 0.1-3%; And / or ZrO2: 0.5-4%, preferably ZrO2: 1-3%; and / or Na2O: 1-6%, preferably Na2O: 2-5%; and / or MgO: 1-4%, preferably MgO: 1-3%; and / or B2O3: 0-2%, preferably B2O3: 0-1%; and / or CaO+BaO+SrO: 0-4%, preferably CaO+BaO+SrO: 0-2%; and / or clarifying agent: 0-1%, preferably clarifying agent: 0-0.5%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3.

27. The glass-ceramic according to claim 17 or 18, characterized in that, Its components, expressed as a weight percentage, contain: Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2%, more preferably Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-1%, and even more preferably does not contain Nb2O5, and / or does not contain WO3, and / or does not contain Bi2O3, and / or does not contain Ta2O5, and / or does not contain TeO2.

28. The glass-ceramic according to any one of claims 17 to 19, characterized in that, The glass-ceramic does not contain P2O5, and / or does not contain B2O3, and / or does not contain SnO2, and / or does not contain SnO.

29. The glass-ceramic according to any one of claims 17 to 19, characterized in that, The glass-ceramic contains a spinel crystal phase, preferably with a higher weight percentage than other crystal phases, more preferably with the spinel crystal phase accounting for 20-50% of the weight of the glass-ceramic, even more preferably with the spinel crystal phase accounting for 30-50% of the weight of the glass-ceramic, and even more preferably with the spinel crystal phase accounting for 30-45% of the weight of the glass-ceramic.

30. The glass-ceramic according to claim 29, characterized in that, The spinel crystal phase is ZnAl2O4.

31. The glass-ceramic according to any one of claims 17 to 19, characterized in that, The glass-ceramic does not contain spodumene crystal phase, and / or does not contain zirconium oxide crystal phase, and / or does not contain quartz crystal phase, and / or does not contain quartz solid solution crystal phase, and / or does not contain Zn2SiO4 crystal phase.

32. The glass-ceramic according to any one of claims 17 to 19, characterized in that, The glass-ceramic has a grain size of less than 70 nm, preferably less than 60 nm, more preferably less than 50 nm, and even more preferably less than 48 nm; and / or a Vickers hardness of 500 kgf / mm. 2 The above values ​​are preferably 600–750 kgf / mm². 2 More preferably, it is 650–750 kgf / mm 2 ; and / or a Young's modulus of 80 to 105 GPa, preferably 85 to 105 GPa, more preferably 90 to 105 GPa; and / or a glass-ceramic with a thickness of less than 2.0 mm, and an average light transmittance of 85% or more at a wavelength of 400 to 800 nm, preferably 87% or more, more preferably 88% or more.

33. A glass cover plate, characterized in that, The product comprises a glass-ceramic article as described in any one of claims 1 to 16, and / or a glass-ceramic article as described in any one of claims 17 to 32.

34. An electronic device, characterized in that, The product comprises a glass-ceramic article as described in any one of claims 1 to 16, and / or a glass ceramic as described in any one of claims 17 to 32, and / or a glass cover as described in claim 33.

35. A display device, characterized in that, The product comprises a glass-ceramic article as described in any one of claims 1 to 16, and / or a glass ceramic as described in any one of claims 17 to 32, and / or a glass cover as described in claim 33.